POLLUTION PROBLEMS IN HUMAN ENVIRONMENT - Gh. H. SANAI (Tehran University of Medical Sciences, 1972)
Since last few decades, the rapid industrialization has led to the development of many new chemicals, namely of which different kind of pesticides are of the most important ones. It is now evident that almost every food, agricultural product, water, soil and human body etc. is contaminated with some sort of chemical or pesticide. In some highly industrialized countries, new ailments have been reported in consequence with the discharge and release of industrial wastes, toxic materials, gases and vapors in the environment. Some chemicals have been found to be carcinogens and/or teratogens while many others like new potent pharmaceuticals, antibiotics, disinfectants, preservatives, artificial coloring maters, flavors, sweetening agents etc. are still of every-day use and yet their ultimate effects in the, long nm on the man's health is not completely known. Today the problem of pollution is of common interest and in case proper safety measures are not achieved there will be the probability of a global intoxication leading to a catastrophe. It is essential that the man should try his best for keeping his environment clean and retain from any sort of contamination through new safe techniques in industry and mass production.